The effect of intermittent fasting 5:2 on IL-6 levels in obese male employees in Jakarta - Diva Octavia Sarah; Karima Yudhistina; Erfi Prafiantini; Lily Indriani Octovia; Novi Silvia Hardiany (Indonesian Nutrition Association, 2023)
Background: Obesity is a condition of excessive fat accumulation in adipose tissue. This condition causes endothelial damage, increase macrophage infiltration, and inflammation in adipose tissue. Inflammation happens due to the increase of interleukin-6 (IL-6) as a proinflammatory cytokine which responsible for the occurrence of chronic diseases. Intermittent fasting is a potentially effective method for losing weight and suggested can reduce levels of proinflammatory cytokines. Objective: The aim of this study is to determine the effect of 5:2 intermittent fasting on IL-6 cytokine levels in obese employees in Jakarta. Methods: This study used a cross-sectional method conducted on 50 healthy male employees aged 19–52 years with a body mass index (BMI) ≥25 kg/m2. Subjects were divided into two groups, the 5:2 intermittent fasting group and the non-fasting group. Intermittent fasting 5:2 was observed every Monday and Thursday for eight weeks. IL-6 levels were obtained through examination using an enzyme-linked immunosorbent assay (ELISA) method. Statistical analysis was performed by Mann Whitney and Kruskal Wallis test. Results: The results showed that the median of IL-6 levels decreased in fasting group from 5,10 (1.06–9.81) pg/mL to 4.64 (1.00–13.39) pg/mL and increased in non-fasting group from 3.65 (1.17–38.70) pg /mL to 6.35 (2.44–19.86) pg/mL, but the change was not significant. Conclusion: Intermittent fasting 5:2 tend to decrease IL-6 levels in obese male employees in Jakarta although the change of IL-6 level was not significant.